Effect of Vascular Injury on Functional Outcome in Knees with Multi-Ligament Injury: A Matched-Cohort Analysis. (20th September 2017) - Sanders, Thomas L.; Johnson, Nicholas R.; Levy, Nathan M.; Cole, Peter A.; Krych, Aaron J.; Stuart, Michael; Levy, Bruce A.
Abstract : Background: Multi-ligament knee injury (MLKI) associated with knee dislocation can result in vascular injury. The purpose of this study was to compare knee function after MLKI between patients with a vascular injury requiring popliteal artery bypass grafting and patients without vascular involvement. Additionally, factors associated with poor knee function in patients who had MLKI with vascular injury were evaluated. Methods: This retrospective study identified patients with an MLKI between 1992 and 2014. Each patient who had a concomitant vascular injury requiring bypass grafting (vascular cohort, n = 16; mean age, 30.3 years) was matched to 2 patients without a vascular injury (control cohort, n = 32; mean age, 31.4 years) on the basis of age, knee dislocation (KD) grade, and peroneal nerve status. Fifteen patients in the vascular cohort and 26 patients in the control cohort had an isolated knee injury. Functional outcomes were assessed with physical examination of range of motion and ligamentous stability as well as patient-reported outcome scores. Results: The vascular cohort had a mean Lysholm score of 62.5 points (range, 16 to 100 points) and a mean International Knee Documentation Committee (IKDC) score of 59.7 points (range, 14.9 to 100 points) at a mean (and standard deviation) of 8.3 ± 5.0 years after surgery. The control cohort had a mean Lysholm score of 86.4 points (range, 51.0 to 100.0 points) and a mean IKDC score of 83.8 points (range, 35.6 to 100.0 points) at a mean of 6.0 ± 4.0 years. The vascular cohort had significantly lower Lysholm (p = 0.001) and IKDC (p = 0.002) scores than the control cohort. A body mass index (BMI) of >30 kg/m 2 was predictive of lower IKDC (p = 0.0009) and Lysholm (p = 0.0008) scores. Conclusions: Patients who sustain an MLKI with an associated popliteal artery injury requiring bypass grafting have significantly lower knee function scores than patients without vascular involvement. This information can be used to help counsel patients with combined multiple ligament and popliteal artery injuries. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.